A Rab-E GTPase Mutant Acts Downstream of the Rab-D Subclass in Biosynthetic Membrane Traffic to the Plasma Membrane in Tobacco Leaf Epidermis - Zheng, Huanquan (American Society of Plant Biologists, 2005)
The function of the Rab-E subclass of plant Rab GTPases in membrane traffic was investigated using a dominant-inhibitory mutant (RAB-E1(d)[NI]) of Arabidopsis thaliana RAB-E1(d) and in vivo imaging approaches that have been used to characterize similar mutants in the plant Rab-D2 and Rab-F2 subclasses. RAB-E1(d)[NI] inhibited the transport of a secreted green fluorescent protein marker, secGFP, but in contrast with dominant-inhibitory RAB-D2 or RAB-F2 mutants, it did not affect the transport of Golgi or vacuolar markers. Quantitative imaging revealed that RAB-E1(d)[NI] caused less intracellular secGFP accumulation than RAB-D2(a)[NI], a dominant-inhibitory mutant of a member of the Arabidopsis Rab-D2 subclass. Furthermore, whereas RAB-D2(a)[NI] caused secGFP to accumulate exclusively in the endoplasmic reticulum, RAB-E1(d)[NI] caused secGFP to accumulate additionally in the Golgi apparatus and a prevacuolar compartment that could be labeled by FM4-64 and yellow fluorescent protein (YFP)–tagged Arabidopsis RAB-F2(b). Using the vacuolar protease inhibitor E64-d, it was shown that some secGFP was transported to the vacuole in control cells and in the presence of RAB-E1(d)[NI]. Consistent with the hypothesis that secGFP carries a weak vacuolar-sorting determinant, it was shown that a secreted form of DsRed reaches the apoplast without appearing in the prevacuolar compartment. When fused to RAB-E1(d), YFP was targeted specifically to the Golgi via a saturable nucleotide- and prenylation-dependent mechanism but was never observed on the prevacuolar compartment. We propose that RAB-E1(d)[NI] inhibits the secretory pathway at or after the Golgi, causing an accumulation of secGFP in the upstream compartments and an increase in the quantity of secGFP that enters the vacuolar pathway.